Research of Scots pine Ukrainian ecotypes in provenance test established in 1975–1976 in Donetsk region - Tereshchenko, L. I.; Prikhodko, O. B.; Los, S. A. (Forestry and Forest Melioration, 2021)
Introduction In 1975–1977 the largest Eurasian transnational network of Scots pine (Pinus sylvestris L.) provenance tests (33 points, 113 origins) was established. On Ukrainian land, the objects of the State network with a total area of 93.3 hectares were laid under the supervision of I. Patlay and P. Zhurova in Kherson, Zhytomyr, Lviv, Kharkiv, and Donetsk regions. The latest research on provenance tests was conducted more than 20 years ago. Determining their current state, productivity, and quality indices is undoubtedly relevant. The aim of the study was to assess the current state, growth dynamics, and development of the ecotypes of Ukrainian origin in Scots pine provenance test in Lyman State Forest Enterprise, Donetsk region, to select provenances that are promising for forest growing in the region. Materials and Methods The 46-year-old stand was investigated in autumn 2020. Continuous or partial measurement of plants in the plots was done according to the variant’s area. The average values of preservation, height, diameter, and qualitative characteristics, condition, and degree of reproduction of trees were assessed within the replications of ecotypes. The control variant was represented by three replications of the Kharkiv ecotype (K-1, K-2, K-3), growing on plots with different micro-environment. The growth dynamics of 22 replications of ecotypes from 3 to 46 years old were assessed using correlation and regression analyses. Results and Conclusions In severe steppe conditions, viability of Ukrainian origins was 28.9 % (from 8.5 % to 63.6 %). There were significant differences in the growth pattern of some geographically allied ecotypes in hilly relief on sandy dry soils. The variability of provenances heights and diameters by replications was average and enhanced, making 18.3 and 26.6%, respectively. In terms of average height, the Cherkasy ecotype (replication II) significantly exceeded the control variants K-1 and K-2. Sumy (pine forest site) (replication I) and Kyiv (replications I, II) ecotypes had growth indexes at the level of control. In terms of the average diameter, none of the ecotypes replications significantly exceeded the control K-1. Prykarpattia and Sumy (replications I) ecotypes were significantly lower; the characteristics of the other variants were at the level of control. The replication II of the Kyiv ecotype had the best average tree trunk volume of 0.23 m3 whilst the average value for the site was 0.11 m3. In terms of productivity An average productivity of pine stand corresponded to site class III, and that of Ukrainian ecotypes corresponded to site classes from I to V. In some cases, the difference between replications was two or three classes of productivity. The relationship between the preservation and the height of replications was described as r = 0.48. The relative stabilization of the ranks of the variants starting from 10 years of age (r = 0.76) was revealed. The measurements at age of 15 allowed predicting the diameter growth for the variants only for 27%. The proportion of straight-trunked trees in variants was from 0 to 24.6 %. The large numbers of pine trees with straight trunks were recorded for Kyiv and Sumy (pine forest site) ecotypes; in Rivne ecotype such trees were absent. The condition and reproduction of most of the represented ecotypes were satisfactory. Trees with cones averaged 15.6% in the variants. Ecotypes from Cherkasy, Kyiv, Sumy (pine forest site), Kharkiv and Donetsk regions were found to be promising for forestry in ravine steppe conditions. The best trees of these origins were recommended to propagate vegetatively for establishing clonal seed orchards.